Development of Android Game-Based Media to Enhance Students' Arabic Grammar Skills - Widodo Febri Utomo; Asrowi Asrowi; Herry Widyastono (Universitas Islam Negeri Palangka Raya, 2025)
The integration of technology into education continues to evolve, with Android-based game media offering new opportunities for more engaging learning experiences. However, there is still a lack of research that specifically focuses on developing Android-based game media to improve Arabic grammar skills at the Madrasah Ibtidaiyah level. This study aims to develop Android-based game media to enhance students’ Arabic grammar skills in Madrasah Ibtidaiyah. Utilizing a Research and Development (R&D) approach with the Alessi & Trollip development model, the research involved media experts, subject matter experts, practitioners, and 40 students. Data were collected through observation and questionnaires, then analyzed using both qualitative and quantitative methods. During alpha testing, the media received an average feasibility score of 91.17% from experts and practitioners, categorized as